Fabrication and testing of composite hierarchical Isogrid stiffened cylinder. (22nd March 2018) - Li, Ming; Sun, Fangfang; Lai, Changliang; Fan, Hualin; Ji, Bin; Zhang, Xi; Liu, Debo; Fang, Daining
Abstract: To get strong, stiff and light cylindrical shell, carbon fiber reinforced hierarchical Isogrid stiffened cylinder (HISC) was designed and fabricated. The cylinder has fractal stiffeners, including the first-order primary Isogrid stiffeners and the self-similar second-order sub-Isogrid stiffeners. The primary Isogrid has thick and high ribs and contains several sub-Isogrid cells whose rib is much thinner and lower. The primary Isogrid improves the bending rigidity of the cylindrical wall to resist the global instability while the sub-Isogrid improves the bending rigidity of the skin enclosed by the primary Isogrid to resist local buckling. The HISC was fabricated by filament winding method based on a silicone rubber mandrel with hierarchical grooves. Axial compression test was performed to reveal the failure mode. With hierarchical stiffeners, the cylinder balances the construction of the skin and the ribs and fails at material failure. Global instability and local buckling are both well restricted by the hierarchical stiffeners.